Brewing Trials of Barley Varieties Registered in the Czech Republic - Mikyška, Alexandr; Psota, Vratislav (KVASNY PRUMYSL, 2017)
Though detailed analysis of malt provides information on the characteristics suitable for its processing in the brewery, the unequivocal relationship between the quality characteristics of the malt and the fi nal, especially sensory, quality of the beer does not exist. The article summarizes the results of three-year pilot brewing tests with the barley varieties recommended for the production of beer with the protected geographical indication “Czech beer” Blanik, Bojos, Francin, Laudis 550, Malz, Petrus and Vendela and varieties for the production of export malts Kangoo, Sebastian, Sunshine and Xanadu. The results showed some specifi c characteristics of the varieties and contributed to the knowledge of the relations between the quality features of the malt and the sensory quality of the Czech lager beer. The analysis of the Principal Component Analysis (PCA) of the sensory quality of beers partly differentiated varieties for "Czech beer" from the varieties for export malts. The color of beers is affected by decoction mashing, the prediction from malt color is inaccurate. A lower attenuation reduces bitterness and sourness of beers. The palate fullness of the beers was positively infl uenced by the total polyphenols and the bitterness of the beers, the bitterness correlated with beer carbonation.